Diagnosis of entry in investigation in students of course 106 of the Military School of Suboficiales Sergento Inocencio Chincá - Barrero Garcia, Julian Enrique (2021)
This research article aims to present an interpretation and analysis of the diagnosis made when starting training in the Research area with students of course 106 of the Military School of Non-Commissioned Officers, the School "Sargento Inocencio Chincá" during the second semester of 2020. An exploratory mixed-type methodology is used, through the survey instrument, which was applied virtually to a population of one hundred students with the aim of knowing the previous knowledge in relation to the research, since within the knowledge that is part of their training is research during the first three semesters of training they receive at the institution; with the objective of directing the educational processes towards the construction of a proposal and research project. This diagnosis is an important part of the teacher's work, since through it the appropriate thematic content, practice and development of activities can be programmed and established that strengthen and enrich the professional profile of the future third corporal of the Colombian National Army. Likewise, outreach proposals are generated in front of imparting pertinent and non-repetitive knowledge with a view to educational quality.